2022
DOI: 10.3390/vehicles4020025
|View full text |Cite
|
Sign up to set email alerts
|

A Way Forward for Electric Vehicle in Greater Bay Area: Challenges and Opportunities for the 21st Century

Abstract: The Greater Bay Area (GBA) accounts for a high percentage of pollution due to the large number of internal combustion engines. In the past few decades, there has been a significant increase in internal combustion engines vehicles while electric vehicles have not taken off yet in GBA. To a certain extent, the acceptance of electric vehicles is still questionable from the industrial practitioners and local communities. As such, this research study aims to identify the challenges and opportunities of electric veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…As such, decision makers and scientists globally are concentrating on sustainable ground transportation to decrease CO 2 emissions and balance the climate. Lau et al [16,17] suggested an energy shift to reduce CO 2 emissions and employ electric vehicles in road transportation. Epicoco and Falagario [13] addressed that the railway is identified as one of the most sustainable and environmentally friendly transport modes, and increasing the efficiency of regional and local railways is a prime sustainable ground transportation goal.…”
Section: Literature Review On Sustainable Ground Transportationmentioning
confidence: 99%
“…As such, decision makers and scientists globally are concentrating on sustainable ground transportation to decrease CO 2 emissions and balance the climate. Lau et al [16,17] suggested an energy shift to reduce CO 2 emissions and employ electric vehicles in road transportation. Epicoco and Falagario [13] addressed that the railway is identified as one of the most sustainable and environmentally friendly transport modes, and increasing the efficiency of regional and local railways is a prime sustainable ground transportation goal.…”
Section: Literature Review On Sustainable Ground Transportationmentioning
confidence: 99%
“…Most of the incentive measures the government has employed are aimed at sustainably expanding the usage of EVs, especially towards nature and our surroundings (Zhang et al, 2017). According to Lau et al (2022), the government of China began using incentives and subsidies many years ago to promote the development of EV infrastructure, including charging facilities. Lau et al (2022) states that at one time, the Hong Kong administration offered 15 billion dollars to the EV industry.…”
Section: Penetration Of Electric Vehicle Into the Greater Bay Areamentioning
confidence: 99%
“…According to Lau et al (2022), the government of China began using incentives and subsidies many years ago to promote the development of EV infrastructure, including charging facilities. Lau et al (2022) states that at one time, the Hong Kong administration offered 15 billion dollars to the EV industry. Recently, the government has subsidized charging utilities (Pan, 2020).…”
Section: Penetration Of Electric Vehicle Into the Greater Bay Areamentioning
confidence: 99%
See 1 more Smart Citation
“…EV's possess various advantages like less pollution, eco-friendly, high efficiency, low maintenance etc. Also considering https://www.indjst.org/ the exponential rise of oil prices across the globe, there is a need to find an alternative solution to the existing internal combustion engine transportation system (2) . Regional and international policies like National Action Plan on Climate Change (NAPCC), Paris Climate Accords etc.…”
Section: Introductionmentioning
confidence: 99%